Aberrant DNA Methylation of FTH-1 and SHOX2 Contributes to Lung Cancer Progression - Salar Tahmasbi; Armin Sadeghi; Habib Zarredar; Milad Asadi; Shahryar Hashemzadeh; Venus Zafari; Hamed Sabbagh-Jadid; Mortaza Raeisi (Middle East Journal of Cancer)
Background: Lung cancer is the most lethal malignancy in the world due to its poor prognosis. DNA methylation change has been identified as a valuable target for cancer, diagnosis, and prognosis. Ferritin heavy chain 1 (FTH-1) and SHOX homeobox 2 (SHOX2) DNA methylation were investigated in non-small cell lung cancer (NSCLC) as novel epigenetic biomarkers.Method: In this case-control study, we initially evaluated the diagnostic value of FTH-1 and SHOX2 DNA methylation, and the Cancer Genome Atlas (TCGA) data on the methylation profile of NSCLC was analyzed. Whole DNA was extracted and bisulfite modification was performed. Then, the methylation status of FTH-1 and SHOX2 was evaluated using quantitative methylation specific polymerase chain reaction (PCR) (qMSP). We used GraphPad Prism version 6.00 program for statistical analysis. Mann-Whitney U test (TCGA-LUNG), paired t-test (internal samples) and receiver operating characteristic (ROC) curve analysis were used to evaluate the statistical differences of DNA methylation between NSCLC tissues samples and adjacent normal specimens (P < 0.05, mean ± SD).Results: TCGA and q-MSP results showed significant FTH-1 hypomethylation and SHOX2 hypermethylation in NSCLC tissues in comparison with margin specimens. Also, FTH-1 and SHOX2 methylation levels were significantly associated with the clinical stage of malignancy. Furthermore, The ROC curve analysis revealed that the area under the curve values for FTH-1 and SHOX2 were determined to be 0.751 and 0.8676, respectively. This indicates the importance of FTH-1 and SHOX2 as diagnostic biomarkers for NSCLC.Conclusion: This study indicates that FTH-1 and SHOX2 methylation could be promising targets for liquid biopsy application of lung cancer.